2015
DOI: 10.1002/2014jb011636
|View full text |Cite
|
Sign up to set email alerts
|

Ground heating and methane oxidation processes at shallow depth in Terre Calde di Medolla (Italy): Numerical modeling

Abstract: The area known as Terre Calde (literally "hot lands") in the plain of the Po River (Italy) is well known for unusual ground temperatures, and up to now, the cause o/f the heating has not been fully investigated. These higher-than-average temperatures are commonly associated with diffuse methane seepage. A detailed study of shallow stratigraphy, temperature profile, and associated gas concentrations and flow rates recently suggested that the observed anomaly could be related to the exothermic oxidation of bioge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
12
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 18 publications
1
12
0
Order By: Relevance
“…This means that, in order to simulate the evolution of porepressure induced by earthquakes, a 3D fluid flow modeling can be very important. 13 Geofluids…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This means that, in order to simulate the evolution of porepressure induced by earthquakes, a 3D fluid flow modeling can be very important. 13 Geofluids…”
Section: Discussionmentioning
confidence: 99%
“…The four layers of the poroelastic half-space have different D values representing a decrease of permeability over depth (Table 1), as proposed by Ingebritsen and Manning [33]. The chosen shallow permeability values are constrained by evidences obtained by drilling [13,18,35]. The resulting dependence of permeability on depth can be expressed as log k ≈ − 12 − 2 9 log z , where k is the permeability (m 2 ) and z is the depth (km).…”
Section: Gps Datamentioning
confidence: 99%
See 1 more Smart Citation
“…The anomalously warm areas are easily recognizable during winter because snow melts within them and during summer when soil heating leads to the death of corn plants (6). Previous studies conducted in 2012 reported a clear correlation between soil heating and gas seepage (CH 4 and CO 2 ) (29). As shown in Fig.…”
mentioning
confidence: 88%
“…2A) indicate that the marked increase in the CO 2 /CH 4 flux ratio is due to the biological oxidation of rising CH 4 , suggesting the occurrence of biological methane oxidation processes in the most aerated layers. Conceptual modeling and numerical simulations have indicated that the exothermic nature of the CH 4 →CO 2 conversion (800 KJ mol −1 of CH 4 ) represents a heat source with the ability to produce the soil thermal anomalies observed in TCM soil (29). This previous finding and thermodynamic prediction prompted us to verify the hypothesized correlation between methanotrophs and soil hot temperatures by examining microbial methanotrophic diversity in TMC soil samples using a cultivation-independent approach.…”
mentioning
confidence: 99%